Risk Analysis of Voltage Violation With PHEV Inter-Area Mobile Charging Strategy Under Gas Station Networks Attacked - Li, Xue; Zhang, Zhourong; Du, Dajun (Frontiers in Energy Research, 2021)
To reduce the risk of voltage violation after gas station networks (GSNs) are attacked, this paper investigates an inter-area mobile charging strategy of plug-hybrid electric vehicles (PHEVs) to decrease the charging load by taking full advantage of charging resource. Firstly, considering the location of the charging station, waiting time and charging fee, an inter-area mobile charging strategy of PHEVs is proposed, and a mobile charging model of PHEVs among regions is established to relieve the charging pressure. Secondly, the risk index is developed to analyze the risk of voltage violation in term of the results of probabilistic load flow (PLF). Finally, the proposed strategy is tested on a modified coastal active power distribution network, and simulation results show that the charging load of PHEVs is dispersed among regions and the risk of voltage over-limit can be declined.